Original articleClinical and neuroimaging correlation of movement disorders in multiple sclerosis: case series and review of the literature - Potulska-Chromik, Anna; Rudzinska, Monika; Nojszewska, Monika; Podlecka-Piętowska, Aleksandra; Szczudlik, Andrzej; Zakrzewska-Pniewska, Beata; Gołębiowski, Marek (Folia Neuropathologica, 2014)
Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system, in which movement disorders (MD) have been reported very rarely. Anatomopathological studies of MS indicate two main processes: inflammation and neurodegeneration. The occurrence of the movement disorders symptoms in MS revises the question of aetiology of these two diseases. During the 10 years of observation in our out-patient clinic and MS units we examined about 2500 patients with clinically definite MS diagnosed according to the revised McDonald’s criteria. Only in 10 cases we found coexistence of MS and MD signs. Below we present rare cases of patients with coexistence of MS and chorea, pseudoathetosis, dystonia and parkinsonism. Searching for the strategic focal lesion in our case series showed demyelinating plaques placed in the thalamus most often. Detailed analysis of the clinical, pharmacological and neuroimaging correlations may help to explain the character of movement disorders in MS.